Encounter with the ’stones’ - LOUIS LAGANA (Journal of Advanced Research in Social Sciences and Humanities, 2018)
Aim: The study focuses on the sculptures of German artist Eva-Gesine Wegner, who spends a lot of time in Malta and creates her works primarily out of stone, wood, and clay. She draws a line between the temples of the Maltese Neolithic era and the statuettes of the goddesses’ bodies found there. Wagner draws parallels between her feelings and the temples, which she sees as symbols of the transcendent. Her sculptures show how she felt connected to female ancestry and how she reacted to the natural world. The spiritual significance of fertility, life, and death permeates her works.Method: Works that evoke prehistoric imagery will be analysed and discussed using Jungian criteria. Incorporating Maria Gimbutas’s theories on the significance of the early European origins and her Goddess philosophy would lend credence to Wegner’s representation of the saint’s woman. A scholar conducts a semi-formal interview with the artist to better comprehend her dedication to the creative process and her fascination with the ancient history of Malta.Findings: The sculptures of Eva-Gesine Wegner are more than just a symbolic connection to antiquity; they evoke emotion, and the artist is undoubtedly attempting to show viewers images that recall maternity, the female aspects of birth, life, and death, and the cycles or role of nature in human existence. She considers the arts to be a spiritual practice. It’s a metaphor for her reaching the pinnacle of her spiritual potential.Implications/Novel Contribution: As this investigation shows, Eva-Gesine Wegner is trying to express her sense of personal and spiritual fulfilment as a woman by connecting her work to the ancient history of Malta.